Comparison of DMSP and SECS region-1 and region-2 ionospheric current boundary. (June 2016) - Weygand, J.M.; Wing, S.
Abstract: The region-1 and region-2 boundary has traditionally been identified using data from a single spacecraft crossing the auroral region and measuring the large scale changes in the cross track magnetic field. With data from the AUTUMN, CANMOS, CARISMA, GIMA, DTU MGS, MACCS, McMAC, STEP, THEMIS, and USGS ground magnetometer arrays we applied a state-of-art technique based on spherical elementary current system (SECS) method developed byAmm and Viljanen (1999) in order to calculate maps of region-1 and region-2 current system over the North American and Greenland auroral region. Spherical elementary current (SEC) amplitude (proxy for vertical currents) maps can be inferred at 10 s temporal resolution, ~1.5° geographic latitude (Glat), and 3.5° geographic longitude (Glon) spatial resolution. We compare the location of the region-1 and region-2 boundary obtained by the DMSP spacecraft with the region-1 and region-2 boundary observed in the SEC current amplitudes. We find that the boundaries typically agree within 0.2°±1.3°. These results indicate that the location of the region-1 and region-2 boundary can reasonably be determined from ground magnetometer data. The SECS maps represent a value-added product from the magnetometer database and can be used for contextual interpretation in conjunction with other missions as well as help with our understanding of magnetosphere-ionosphere coupling mechanisms using the ground arrays and the magnetospheric spacecraft data. Highlights: We examine SECS and space based observations of 110 region-1 and region-2 boundaries. We demonstrate the both ground and spacecraft observations produce similar results. We discuss possible reasons for differences. SEC maps can be used for contextual interpretation. SEC maps can help with our understanding of M–I coupling mechanisms.